Separated by Bars or Dollar Signs? A Comparative Examination of the Financial Literacy of Those Incarcerated and the General Population - Glidden, Marc D. (American journal of criminal justice, 2017)
This study examines the level of financial literacy of inmates in Arkansas correctional institutions. Furthermore, it compares the financial knowledge, planning, and practices between not only white and non-white inmates but also between males within and outside of penal institutions. Specifically, this research combines primary data on the financial realities of those within correctional institutions and existing statistics on the public to examine the relationship between demographics, banking history, use of non-traditional lenders, and financial literacy. While prior literature on the public is extensive, research on the financial literacy of individuals currently incarcerated is sparse. Findings indicate vast differences between the public and those within penal institutions, particularly in financial knowledge and planning. For our incarcerated sample we find similar disparities between our white and non-white respondents. Last, we find that youth, minority status, and lowered education are predictors of lower financial knowledge, use of predatory lender use, and poor financial planning among inmates. This is crucial because low levels of financial literacy, use of predatory lenders, and poor financial planning often provide barriers to asset accumulation, which increases the probability of incarceration and recidivism.